2018
DOI: 10.1155/2018/5167829
|View full text |Cite
|
Sign up to set email alerts
|

MiR-30a: A Novel Biomarker and Potential Therapeutic Target for Cancer

Abstract: MicroRNAs (miRNAs) are small, highly conserved noncoding RNAs molecules, consisting of 18–25 nucleotides that regulate gene expression by binding to complementary binding sites within the 3′untranslated region (3′UTR) of target mRNAs. MiRNAs have been involved in regulating gene expression and diverse physiological and pathological processes. Several studies have reported that miR-30a, situated on chromosome 6q.13, is produced by an intronic transcriptional unit. Moreover, miR-30a has demonstrated its role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 75 publications
(101 reference statements)
3
57
0
Order By: Relevance
“…[5,20,21] MicroRNAs (miRNAs) are short non-coding RNA approximately 19-25 nucleotides in length, which directly bind to the 3 0 -UTR of target mRNAs to regulate gene expression, either through degradation of the RNA or translation inhibition. [22,23] MiRNAs participate in diverse molecular and cellular processes, such as cellular migration/invasion, cell growth, apoptosis and signal transduction. MiRNAs dysregulation is a hallmark of many cancers, including glioblastoma, and they can be classified into tumour-suppressive miRNAs and onco-miRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…[5,20,21] MicroRNAs (miRNAs) are short non-coding RNA approximately 19-25 nucleotides in length, which directly bind to the 3 0 -UTR of target mRNAs to regulate gene expression, either through degradation of the RNA or translation inhibition. [22,23] MiRNAs participate in diverse molecular and cellular processes, such as cellular migration/invasion, cell growth, apoptosis and signal transduction. MiRNAs dysregulation is a hallmark of many cancers, including glioblastoma, and they can be classified into tumour-suppressive miRNAs and onco-miRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous pieces of evidence show that abnormal expression of miRNAs and their regulation play important roles in the initiation and progression of human cancers, such as esophageal carcinoma, hepatocellular carcinoma and breast carcinoma . Some miRNAs, such as miR‐30a, are able to affect many types of malignancies and can be used as biomarkers for these tumors . To date, multiple miRNAs have been shown to have vital functions in the development of NSCLC, but few of these miRNAs could be a candidate for targeted therapy, and the specific underlying mechanisms for their effects in the tumorigenesis and progression of NSCLC are still not understood.…”
Section: Introductionmentioning
confidence: 99%
“…9 Some miRNAs, such as miR-30a, are able to affect many types of malignancies and can be used as biomarkers for these tumors. 10 To date, multiple miRNAs have been shown to have vital functions in the development of NSCLC, 11,12 but few of these miRNAs could be a candidate for targeted therapy, 13 and the specific underlying mechanisms for their effects in the tumorigenesis and progression of NSCLC are still not understood.…”
mentioning
confidence: 99%
“…The miR‐30a has been demonstrated to play an important role in biological processes, including cancer proliferation, metastasis, and apoptosis. Moreover, miR‐30 is also involved in several signal pathways to regulate autophagy or drug susceptibility (Jiang, Zhang, & Tang, ). The previous study reported that miR‐30 regulated Toll‐like receptor (TLR)/MyD88 activation and cytokine expression in THP‐1 cells during Mycobacterium tuberculosis infection (Wu, Sun, & Dai, ).…”
Section: Discussionmentioning
confidence: 99%